Changes in Lipid Profiles of HIV+ Adults over Nine Months at a Harare HIV Clinic: A Longitudinal Study. (8th March 2016) - Zhou, Danai Tavonga; Nehumba, Doreen; Oktedalen, Olav; Marange, Princess; Kodogo, Vitaris; Gomo, Zvenyika Alfred; Esterhuizen, Tonya M.; Stray-Pedersen, Babill
Abstract : HIV infection, together with ART, is associated with changes in biochemical, metabolic parameters and lipid profiles. The aim of this study was to compare changes in lipid profiles among HIV positive outpatients over nine months. 171 patients were investigated, 79% were ART experienced, and 82% of ART experienced patients were on NVP/EFV first line at baseline, but some patients changed ART groups over follow-up and classification was based on intent to treat. More than 60% ART naïve and ART experienced patients had some form of dyslipidemia either at baseline or at follow-up, but mean lipid values for the two groups were within normal limits. At baseline and follow-up, mean levels of TC and HDL were slightly higher in the ART experienced group. Interestingly, there was higher increase in HDL over time in the ART negative group compared to the ART positive group. There was a decrease in TC/HDL ratio in both groups over time, suggesting a reduction in calculated risk of CHD over time. HIV positive patients frequently show various forms of dyslipidemia, but there are no changes in average atherogenic lipid levels and results suggest reduced risk of CHD, mainly due to increases in HDL, after nine months of observation time.